Multiphysical numerical analysis of electromagnetic devices: state-of-the-art and generalization - Pantelyat, M.G. (Електротехніка і електромеханіка, 2013)
In this paper, an analysis of state-of-the-art and an attempt to generalize the basic principles of multiphysical (coupled) computer simulation of various electromagnetic devices (electrical machines, induction heaters, actuators, electrophysical devices, etc.) are presented. The analysis is based on the author’s wide experience in solving various practical problems regarding design and operation of a variety of innovative machines and devices as well as on studies carried out by other researchers.